How Do Parents Introduce Basic Mathematics to Down Syndrome Children? - Siron, Yubaedi; Rahmah, Aulia; Nadiyah, Hadiyatun; Resti Alawiyah, Hani; Alfiyanti, Nia; Fajriah, Syifa (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2022)
Purpose – This study aims to analyze the involvement of parents in introducing basic mathematics to children with down syndrome.Design/methods/approach – This study uses a qualitative approach by conducting online interviews with parents of children with down syndrome. Participants were determined using purposive sampling involving five parents. This study reveals that the involvement of parents in introducing basic mathematics to children with down syndrome has different variants. Collecting data was using semi-structured interviews with interview guidelines, recorders, and documentation. Data analysis used the Milles and Huberman model.Findings – Parents initiate methods and media in introducing basic mathematics to children. Parents can also identify the child's response, identify the advantages and disadvantages of the media, and provide alternative solutions to the obstacles and challenges faced.Research implications/limitations – This study explains introducing strategic basic mathematical abilities in children with down syndrome and the involvement of parents in educating children with down syndrome in basic mathematics.Practical implications – Parents of children with down syndrome need to introduce children to math early on. Parents have an essential role in introducing their down syndrome children's basic mathematical abilities by utilizing the media and giving good responses.Originality/value – This research contributes to educating children with down syndrome in basic mathematics. Paper type: Case study